Mechanical insights into biomaterial wound healing patches and polyvinyl acetate elasticity / Muhammad Iman Sufi Suliman .. [et al.] - Suliman, Muhammad Iman Sufi; Mohd Nazali, Nur Nabila; Abdul Wahab, Abdul Malek; Adull Manan, Nor Fazli; Khalit, Muhammad Ilham (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
This study investigates the development of biomaterial healing patches, specifically focusing on the elastomer characteristics and hyperelastic parameters of polyvinyl acetate in lab-made skin. Three sets were evaluated: plain PVAc (Set A), a mix of PVAc with Polysiloxanes (Set B), and a combination of PVAc with PVM-MA &CMC (Set C). Mechanical properties and hyperelastic behavior were assessed using ASTM D412 type-C standard and a 40 mm/min tensile test. Set A shows higher tensile stress (0.072 MPa) and higher tensile strain (1.1324) than Sets B and C. The Mooney-Rivlin and Ogden models were identified as suitable for elastomer characteristics among various hyperelastic models; specific constants for Set A were validated through these models: μ = -0.0211, α = -2.2919 for the Ogden model, C1 = -0.0036, C2 = 0.0300 for the Mooney-Rivlin model. These findings reveal similarities in mechanical characteristics between studied materials previously developed to mimic skin seen in the pattern of the hyperelastic graph, which has significant implications in developing skin-mimicking compounds for medical applications. The paper establishes potential advances in surgical practices through medicinally treated artificial skin but underscores further research into behavior when used within artificial skins in this technology sector.